Effect of the Lactation Number during Transition Phase on Various Physico-Chemical, Compositional and Microbiological Characteristics of Bovine Colostrum - Nazir, Tahir; Pal, Mohammad Ashraf; Manzoor, Ashaq; Maqbool, Irshad; Mir, Bilal Ahmad; Sofi, Asif Hassan (International Journal of Livestock Research, 2019)
The current study was undertaken to study the effect of lactation number on quality of bovine colostrum under temperate conditions. It was found that the specific gravity, fat, total protein, lactose and total solids content of the colostrum samples from second lactation cows were significantly (p ≤ 0.05) lower than other lactations. Casein protein, whey proteins, solids not fat and electrical conductivity were comparable among different lactations. The specific gravity of the colostrum samples from first lactation cows was significantly (p ≤ 0.05) higher than other lactation cows. The ash content of the colostrum samples of fourth lactation was significantly (p ≤ 0.05) higher than first and second lactation however it was comparable other lactation samples. The pH the colostrum samples from fifth lactation cows was significantly (p ≤ 0.05) lower than other lactations which among themselves possessed comparable (p > 0.05) values. The total plate count (TPC) of the colostrum samples from sixth lactation cows was significantly (p ≤ 0.05) higher than other lactations which among themselves possessed comparable (p > 0.05) values.